The Spatial Differences of Modernisation in Hungary at the Beginning of the 20th Century - Beluszky, Pál (Discussion Papers, 2012)
Hungary, during its history, has made several attempts to catch up with the Western European countries, the so-called ‘modern world’. In most cases ‘his¬tory’ has doomed these efforts to failure, and with this, modernisation (i.e. the catch up proc¬ess) was determined to stop for decades and even for centuries. The „catch up” process was possible only by the elimination of feudal circumstances, and by the establishment of civil laws and order, the passing of proprietorship acts in 1848. Since that period, the modernisation with harmonisation process with Western industrial societies progressed at an increased speed. This process showed a significant improvement at the turn of the century and in the period before World War I. Yet, the „catch up” process within Hungary was character¬ised by significant spatial differences. This essay is an attempt for the assessment of these spatial differences in Hun¬gary, which became significant by the turn of the 19th and 20th century.